A rare case of collision tumor of thyroid gland: simultaneous occurrence of calcitonin negative medullary thyroid carcinoma and papillary thyroid carcinoma - Saharan, Savita; Solanki, Ranjana; Saharan, Deepak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Medullary thyroid carcinoma and papillary thyroid carcinoma are two distinct types of thyroid carcinoma having different cellular origin. The simultaneous occurrence of two distinct neoplasms termed “collision tumour” and it is a rare entity. Sometimes the medullary component does not show calcitonin positivity and hence this becomes a very rare entity. Herein we describe a very rare case of simultaneous occurrence of calcitonin negative medullary thyroid carcinoma and papillary thyroid carcinoma.